Effects of separating commercial and investment banking: Evidence from the dissolution of a joint venture investment bank - Akiyoshi, Fumio (Journal of Financial Economics, 2019)
This study investigates how firms are affected by the separation of commercial and investment banking, using unique data from the dissolution of Japan’s Daiwa Securities SMBC, a joint venture investment bank. This event prevented its client firms from receiving a combination of lending and underwriting services. After the dissolution, these firms experienced a sharper decline in market value, more frequent switching of seasoned equity offering (SEO) underwriters, and the disappearance of lower SEO discounts when they had close lending relationships with Sumitomo Mitsui Financial Group, the ex-parent commercial bank. Thus, separating the two banking businesses would impose costs on firms.